The Effectiveness of Constitutional Complaint as a Domestic Remedy for the ECHR Violations - Zombory, Katarzyna (The ECHR at 70: The Central European Narrative, 2025)
This article explores the effectiveness of constitutional complaint procedures as domestic remedies within the meaning of Articles 13 and 35 para. 1 of the European Convention on Human Rights (ECHR). It examines the standards applied by the European Court of Human Rights (ECtHR) to domestic remedies in general, as well as the specific criteria relating to constitutional complaints, in order to determine what criteria are applied to assess their effectiveness. The paper focuses on the Hungarian and Polish models of constitutional complaint and analyzes the ECtHR’s relevant case-law to establish whether, and under what circumstances, constitutional complaint procedures in these two Central European countries can be considered effective domestic remedies within the meaning of Articles 13 and 35 para. 1 of the ECHR. The analysis shows that the ECtHR’s assessment of the effectiveness of constitutional complaints can shift over time, departing from an objective legal framework toward a broader and more ambiguous evaluation of institutional and political developments affecting constitutional adjudication.Keywords: right to effective remedy, Article 13 ECHR, constitutional complaint, Poland, Hungary, European Court of Human Rights